2016
DOI: 10.1002/jpln.201600153
|View full text |Cite
|
Sign up to set email alerts
|

Localized application of sewage sludge improved plant nitrogen and phosphorus uptake by rhizobox‐grown spring wheat

Abstract: Sewage sludge (SS) can be used as an alternative fertilizer in agriculture. It is normally broadcasted and plowed into soil, but it is not clear if it has a potential as a placement fertilizer. A rhizobox experiment was conducted to investigate the placement effect of SS and mineral nitrogen (N) fertilizer on shoot and root growth as well as nutrient uptake of spring wheat (Triticum aestivum L.). The treatments included localized SS, mixed SS, localized SS and ammonium, localized ammonium, and a control withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…As mudas de aroeira costumam responder bem à adubação orgânica independente do resíduo orgânico utilizado [14]. Além disso, a utilização de lodo de esgoto na composição do substrato está relacionada com o favorecimento do crescimento vegetal, por aumentar a disponibilidade de nutrientes, principalmente de fósforo e nitrogênio [20].…”
Section: Discussionunclassified
“…As mudas de aroeira costumam responder bem à adubação orgânica independente do resíduo orgânico utilizado [14]. Além disso, a utilização de lodo de esgoto na composição do substrato está relacionada com o favorecimento do crescimento vegetal, por aumentar a disponibilidade de nutrientes, principalmente de fósforo e nitrogênio [20].…”
Section: Discussionunclassified
“…The side of each large pot was then covered with aluminium foil to provide shade. While ultrapure water was added two or three times a week to maintain a water‐holding capacity at 60% in the soil (Kong et al., 2013; Wang, Jensen, et al., 2016), the seedlings were thinned to one plant per pot within one week of germination. The plants were grown for 28 days at a controlled temperature (25°C) with a 14‐h photoperiod using a 40‐W horticultural lamp.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, the partial distribution of organic matter can also trigger root structure alterations. Wang, Jensen, et al (2016) reported that the localized application of sewage sludge compost caused a high root development, enabling the efficient utilization of phosphorus and nitrogen derived from the compost. These findings suggest that root responses differ depending on the partial distribution of fertilizer in the combined application of animal manure compost.…”
Section: Introductionmentioning
confidence: 99%